Políticas públicas e práticas sociais direcionadas a inclusão das pessoas com deficiência: retrato da realidade do Estado da Bahia, início do século XXI - Santana, Nivaldo Vieira de (2008)
This thesis is the result of a research which had the aim of identifying, analyzing and understanding the praxis of the processes which lead the insertion/inclusion of handicapped people understood as those who have hindrances of physical, intellectual or sensorial nature, in the State of Bahia, in this beginning of the 21st century. One starts from the hypothesis that the inclusion/insertion and/or exclusion process of this population segment is, as a sociocultural phenomenon, crossed by political processes, so that, because of the sense given to certain ways of thinking, the perspectives of social coexistence can reaffirm discriminative and prejudiced processes, thus influencing so that institutional ways of conveying cultural values become insufficient to guarantee their political and social belonging. In order to prove it, one carries out an interpretative, critical and historical study by means of theoretical surveys, analysis of official documents intercalated with field research in three municipalities in Bahia: Salvador, the capital and the precursor of the State policies; Serrinha, which lives a state of absolute absence of policies compatible with the inclusion process; and Vitória da Conquista, which counts on reasonable attendance policies. Thus, one gets to a circumstantial diagnosis of the phenomenon, whose data and interpretations served to understand the sense given to the reality of the handicapped when submitted to jurisprudence and social contracts, which leads us to inventory and analyze documents for laws in relation to the life conditions and ways of coexistence of the so called handicapped. The thesis is made up of three chapters. The first one presents a theoretical conceptual outline constituted by authors such as Berger and Luckmann, Hannah Arendt, Norberto Bobbio and Pierre Bourdieu. The second one presents an inventory and analysis of documents related to the jurisprudence and social contracts with the purpose of identifying and contextualizing the modes how the sociocultural thought which founds the idea and the inclusivist ideal is constructed; and the last one presents a circumstantial diagnosis, a result of field research founded on participant observation and on semi-structured interviews. It is concluded that there are changes of meaning when laws and legal determinations are submitted to the reality which expresses itself in the social practice, which leads to understand that the modes and the institutional ways of building and conveying conceptions about the inclusivist process, besides not assuring changes in the sociopolitical, economical and material reality, are insufficient to guarantee their social belonging